Comparative analysis of medications for antibiotic therapy of chronic obstructive pulmonary disease in the pharmaceutical market of Ukraine and France - L. I. Budniak; N. P. Darzuli (Zaporozhye State Medical University, 2020)
The aim of the work - comparative analysis of the assortment of registered medicines for antibiotic therapy of chronic obstructive pulmonary disease (COPD) in the domestic market and similar segment of the French market. Materials and methods. The study of drug assortment in Ukraine was carried out according to the State Register of Medicines of Ukraine, employing the directory of medicines Compendium online, Anatomical Therapeutic Chemical Classification, web-resource Tabletki.UA. Database Base de données publique des médicaments was consulted while studying the pharmaceutical market in France. The following methods were used: information search, marketing analysis, graphical, comparative and logical methods. Results. A comparative analysis of medicines employed in Ukraine and France for antibiotic therapy of chronic obstructive pulmonary disease (COPD) was performed. Conclusions. Pharmaceutical markets of drugs for antibiotic therapy of COPD in Ukraine and France are analyzed. As of January 2020, there are 43 brand names (BN) of medicines with 73 available range items registered in Ukraine, and 87 BN medicines with 150 available range items registered in France. The analysis of drugs assortment showed that foreign drugs predominate in Ukraine and France, their share is 84 % and 55 %, respectively. Among the drug-importing countries, the leaders in Ukraine are India and Germany, and in France they are Spain, England and Germany. The share of domestic drugs in Ukraine and France is lower - 16 % and 45 %, respectively. The leaders among domestic manufacturers in Ukraine are Yuria-Pharm LLC and Astrapharm LLC, in France they are Sanofi Winthrop Industrie, Mylan S.A.S., Delpharm Tours, Delpharm Lille S.A.S. and Panpharma. In the two countries, the majority of drugs for COPD antibiotic therapy treatment is manufactured as powders for solutions and injections, and as tablets; their share in Ukraine is 41 % and 33 %, in France - 19 % and 59 %, respectively. Monocomponent drugs prevail in Ukraine and France. Since the Ukrainian pharmaceutical market, in comparison with the French drug market, is significantly dominated by foreign drugs, it is important to develop new domestic drugs that would be used in COPD treatment.